Effect of stage of maturity and frying time on the quality of Banana springs - S. M. Karim, Rezaul; Rahmatullah, Noorjanna; Mad Nordin, Mariam Firdaus; Karim Rajin, S. M. Ataul (Universiti Putra Malaysia Press, 2018)
Banana springs are a new snack food similar to banana chips. This study focuses on the quality improvement of banana springs. The effects of stage of maturity and time of frying on the quality of banana springs prepared from two varieties namely, Musa acuminata Colla cv. Berangan and Musa paradisiaca L. cv. Nangka, were evaluated. Five stages of maturity, i.e., i) mature, ii) early ripening, iii) intermediate ripening, iv) ripe, and v) overripe, were used in the trial. The total soluble solid (TSS) of two varieties at different maturity stages was measured. Banana springs were made by using spiral potato slicer. The slices of banana spring were 2±0.1 mm in thickness. The banana springs were deep fried in refined, bleached and deodorised (RBD) palm olein at a temperature of 170o C for 0, 3, 4, 5, and 6 minutes respectively. The fried banana springs were tested for their texture and crispiness. The samples were assessed for colour, flavour, texture, taste and overall acceptability by a 30-member taste panel. The TSS content of Nangka banana was greater than Berangan banana and the TSS content increased with maturity but it was a bit different between two varieties. Banana springs of Nangka variety had a higher value for texture (hardiness), especially at the early maturing stages in comparison to Berangan banana. Frying of banana springs for five and six minutes produced the same quality. An acceptable product with good taste, crispness, and the odour was obtained from both the varieties when fried at 170o C for 5 minutes. Nangka banana was better in respect of sweetness, odour, texture, and crispness vis-a-vis Berangan. Green matured banana (Maturity index I) of both the varieties was found suitable for the preparation of quality banana springs.